Mengontrol Diri dalam Menghadapi Persoalan Pendidikan pada MahasiswaÂ - Saman, Muhamad (Jurnal Ilmiah Psyche, 2018)
The purpose of this study to determine the relationship of emotional control with problem solving in the education of students of the Department of Psychology of Islam. The study population of students majoring in Islamic Psychology Faculty of Islamic Theology and Islamic Thought UIN Raden Fatah Palembang amounted to 200 people. Of the population, the sample is taken as many as 127 students. Measuring devices used in the form of a scale of emotional control and problem solving. Analysis of data using linear regression tool SPSS Version 20. The results showed a correlation coefficient 74,1% with a coefficient of determination. Thus the hypothesis that there is a relationship between emotional control with problem solving in the education of students of Islamic Psychology Department Faculty of Islamic Theology and Islamic Thought UIN Raden Fatah Palembang proven true. Therefore, control of emotions can be done at the time of solving the problems faced by students.